Analisis Putusan Kumulasi Perkara Perceraian Dan Harta Bersama Di Hubungkan Dengan Undang-Undang Nomor 50 Tahun 2009 Tentang Perubahan Kedua Atas Undang-Undang Nomor 7 Tahun 1989 Tentang Peradilan Agama - Nabila, Gina; Bunyamin, Bunyamin (UNES Law Review, 2024)
This research is motivated by the fact that resolving disputes regarding joint property in the household which can no longer be maintained is to resolve them peacefully by making a deed of agreement between the disputing parties, that would be better and fair. The purpose of this research is to determine the analysis of cumulative decisions on divorce cases and joint property linked to Law Number 50 of 2009 concerning amendments to Law Number 7 of 1989 concerning Religious Courts. This research uses descriptive analytical methods with a normative juridical approach. The results of the research show that after developing resources, infrastructure and technology, the court needs to provide education and training for the parties involved in the lawsuit accumulation process so that they understand the legal process that will be taken in order to increase the quality of management and the ability to analyze appropriately so that errors do not occur so there must be process delays, and most importantly the court must carry out continuous evaluation and revision to create fast, simple and low-cost principles. The entire authority of the Religious Courts is determined by Law Number 50 of 2009 regarding the revision of Law Number 7 of 1989 regarding Religious Courts. Among them are marriage, divorce due to divorce, contested divorce, inheritance, wills, grants, endowments, zakat, infaq, alms, and sharia economics. Regarding what is included in the scope of marriage, the settlement of divorce lawsuits and joint property is included in it, especially in the explanation of points 9 and 10.